A STUDY OF FACTORS RELATED TO HEALTH BEHAVIORS OF PEOPLE WITH RISK OF DIABETES IN UTHAITHANI - Kaewjongprasit, Phiphat (Journal of MCU Nakhondhat, 2023)
The purposes of this research were to study health behavior and factors related to health behaviors of people with risk for diabetes in Uthai Thani Province. Using a correlational research model. The sample group consisted of 376 people in the diabetes risk group aged 35 years and over who passed a verbal screening test and had a blood test result between 100 - 123 mg/dl, residing in Uthai Thani Province. The sample was selected by systematic random sampling. Research tools is a questionnaire created by the researcher consisting of 4 parts: 1) general information 2) questionnaire about knowledge of diabetes (reliability = 0.78) 3) questionnaire perception about diabetes (reliability = 0.87) and 4) health behavior questionnaire to prevent diabetes (reliability = 0.83). Analyze data Using frequency statistics, percentage, mean, standard deviation. and Pearson's correlation coefficient. The results of the research found that 1) health behavior of people at risk for diabetes in Uthai Thani Province is at a moderate level. 2) Knowledge about diabetes, Perceived Susceptibility of diabetes, Perceived severity of diabetes, Perceived benefits of practices to prevent diabetes, and Cues to action, There were a positive relationship with health behaviors to prevent diabetes at a high level, with statistical significance at the .01 level (r = .711, .703, .681, .663 and .640, respectively). Perceived barriers to diabetes prevention practices were positively related to health behaviors to prevent diabetes. at a moderate level Statistically significant at the .01 level (r = .572). Therefore, information obtained from research should be used to organize activities to change health behaviors so that at - risk groups do not become patients.